Professional centred shared decision making: Patient decision aids in practice in primary care - Murtagh Madeleine J; Thomson Richard G; Burges Watson Duika (BMC, 2008)
Abstract Background Patient decision aids are increasingly regarded as important components of clinical practice that enable shared decision making (SDM) and evidence based patient choice. Despite broad acceptance of their value, there remains little evidence of their successful implementation in primary care settings. Methods Health care practitioners from five general practice surgeries in northern England participated in focus group sessions around the themes of patient decision aids, patient and practitioner preferences and SDM. Participants included general practitioners (n = 19), practice nurses (n = 5) and auxiliary staff (n = 3). Transcripts were analysed using a framework approach. Results We report a) practitioners' discussion of the current impetus towards sharing decisions and their perspectives on barriers to SDM, and b) the implementation of patient decision aids in practice and impediments such as lack of an evidence base and time available in consultations. Conclusion We demonstrate two orientations to sharing decisions: practitioner-centred and patient-centred with the former predominating. We argue that it is necessary to rethink the changes required in practice for the implementation of SDM.